Ograniczenia informacyjne w procesie kalkulacji ekonomicznej wartości dodanej (EVA) - Nowicki, Jarosław (Problems Connected with Access to Data During the Estimation of Economic Value Added (EVA), 2005)
The article presents problems connected with access to data during the estimation of economic value added (EVA). The biggest emphasis is put on problems with calculation of net operating profit after taxes (NOPAT) and invested capital (IC). Issues presented in this article are particularly interesting, since EVA is one of the most popular methods of measuring the effect of shareholders' value creation in companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 320-331